Improving Students’ Speaking Skill through Think Pair Share Strategy - Putri Fatimah Abubakar (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2023)
This research was conducted with the aim of testing the effectiveness of the Think-Pair-Share strategy (one of the strategies in the Cooperative Learning Model) in improving students' speaking skills. This study was designed as classroom action research conducted in the English Education study program at STKIP Kie Raha Ternate. 13 out of 26 students participated in the study to take tests and interviews. The researcher also observed the teaching and learning process in the classroom to get details of the learning activities. The data collected by the researcher was then interpreted using a speaking rubric that was validated by the expert. Based on data analysis, the researcher found that the students' speaking ability experienced a significant increase after going through several speaking learning activities using the Think Pair Share strategy. The reasons behind students' difficulties in speaking are also discussed.